Gender discrimination at the workplace: a review of Airasia BHD V Rafizah Shima Bt Mohamed Aris - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2015)
Discrimination implies unfair treatment of two or more persons or subjects on grounds such as race, gender, disability, age, religious belief, etc.2 Gender discrimination exists when women, for example, are treated less favourably or suffer detrimental treatment at the workplace as a result of unreasonable differential treatment between men and women. The International Labour Organisation (‘ILO’) considers discrimination as ’a differential and less favourable treatment of certain individuals’ because of any characteristics such as sex, race and religion, ‘regardless of their ability to fulfil the requirements of the job’.3 The United Nations Universal Declaration of Human Rights 1948 (‘UDHR’) provides that all human beings are born free and equal in dignity and rights. Discriminatory practices in the workplace in terms of promotion, job assignment, leave entitlement and termination, among others, are prohibited by the United Nations Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). This article briefly ventures to discuss the recent Court of Appeal’s decision in AirAsia Bhd v Rafizah Shima bt Mohamed Aris and how the philosophy underlying CEDAW should have been addressed.